Self Help Groups (SHGs) and Women’s Development: A Case Study of the Varanasi District, India - Tripti Kumari; Anand Prasad Mishra (Space and Culture, India, 2015)
Development is a multi-dimensional process that affects society in multiple ways. It is well documented that women constitute about half of the world’s population but their share in the economy and other development spheres remain neglected. In addition, this large section of population (including Indian women) have been suffering from various disadvantages - lack of accessibility to resources, non-recognition of their economic contribution within the family and society. In order to resolve these emerging challenges, Government of India (GOI) has implemented various programmes and policies since Independence. Among these programmes, Self Help Groups (SHGs) may be considered as a significant initiative of the government as well as the non-governmental organisations (NGOs). These are based on the principle of democratic process of development. The democratic institution provides a platform to the socially and economically deprived sections and encourages them for economic participation. Since the 1970s, SHGs have been working in many states of India and contributing to the development processes. The present paper is an attempt to analyse the contribution of SHGs in women’s development in the district of Varanasi in Uttar Pradesh. The impact of these groups on women’s development has been analysed by Gender Development Index (GDI), which focused on the male-female differences in terms of longevity of life, knowledge and economic betterment.